2002
DOI: 10.1109/tcsii.2002.1013866
|View full text |Cite
|
Sign up to set email alerts
|

Design of high-speed multiplierless filters using a nonrecursive signed common subexpression algorithm

Abstract: In this work, a new algorithm called nonrecursive signed common subexpression elimination (NR-SCSE) is discussed, and several applications in the area of multiplierless finite-impulse response (FIR) filters are developed. While the recursive utilization of a common subexpression generates a high logic depth into the digital structure, the NR-SCSE algorithm allows the designer to overcome this problem by using each subexpression once. The paper presents a complete description of the algorithm, and a comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(57 citation statements)
references
References 13 publications
0
57
0
Order By: Relevance
“…We also tested the algorithms on a set of FIR filters, and the results are tabulated in Table 5. We compared our methods with the delay aware subexpression elimination methods proposed by [8], which was the only other method that performed such an optimization. Their method can only be applied to single variable systems such as the transposed form of the FIR filters, and they assure delay optimality by restricting their common subexpressions to be only non-recursive.…”
Section: Experiments With the Delay Aware Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…We also tested the algorithms on a set of FIR filters, and the results are tabulated in Table 5. We compared our methods with the delay aware subexpression elimination methods proposed by [8], which was the only other method that performed such an optimization. Their method can only be applied to single variable systems such as the transposed form of the FIR filters, and they assure delay optimality by restricting their common subexpressions to be only non-recursive.…”
Section: Experiments With the Delay Aware Algorithmmentioning
confidence: 99%
“…Most of the earlier works for finding common subexpressions in systems involving constant multiplications were based on finding common digit patterns in the set of constants multiplying a single variable [1][2][3][4][5][6][7][8][9]. These methods are good enough for optimizing systems where only single variable optimizations are required, such as the transformed form of FIR digital filters.…”
Section: Introductionmentioning
confidence: 99%
“…1024-point FFT) then poor layout regularity may result from complex wiring of sub-expressions from taps large distances apart in the data vector. Indeed a recent paper has shown that choosing such sub-expressions can result in a speed reduction and greater power consumption [7]. It is therefore sensible to divide each N -point dot product into N/r sub rpoint dot product chunks, where r < N and r ∈ Z Z, and optimise each chunk independently.…”
Section: Ppstmentioning
confidence: 99%
“…In [1][2][3][4][5][6], various approaches have been proposed to reduce the area by replacing the multiplications with minimal hard-wired shifts, adders, and subtractors. The quantization effects of coefficients and round-off noise in multiplication have been analyzed in [7] and [8], respectively.…”
Section: Introductionmentioning
confidence: 99%